2022
DOI: 10.1002/gps.5713
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain and long‐term dementia risk in older adults: Results from a 24‐year longitudinal study

Abstract: Introduction: Chronic pain (CP) was associated with cognitive impairment in previous studies. However, the longitudinal association between CP and dementia remains under debate. We aimed to assess the prospective link between CP and long-term dementia risk in a population-based cohort of older participants, considering covariables linked to CP and cognitive functioning. Methods:The study sample was selected from the PAQUID study, an ongoing cohort of older community-dwellers aged 65 years and over at baseline;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…It is worth noting that in both our studies, CP was mainly located in joints, dorso-lumbar site, and limbs, with less than 5% located in the head site. 4 Taken together, these results suggest that the presence of moderate or severe CP does not seem to be associated with accelerated cognitive decline affecting all cognitive functions but specifically processing speed, cognitive speed known to be a nonspecific marker of global brain health. Similarly, CP is not associated with long-term dementia risk.…”
Section: Reply To Dos Santos Ferreira and Vellymentioning
confidence: 70%
See 1 more Smart Citation
“…It is worth noting that in both our studies, CP was mainly located in joints, dorso-lumbar site, and limbs, with less than 5% located in the head site. 4 Taken together, these results suggest that the presence of moderate or severe CP does not seem to be associated with accelerated cognitive decline affecting all cognitive functions but specifically processing speed, cognitive speed known to be a nonspecific marker of global brain health. Similarly, CP is not associated with long-term dementia risk.…”
Section: Reply To Dos Santos Ferreira and Vellymentioning
confidence: 70%
“…It is worth noting that in both our studies, CP was mainly located in joints, dorso-lumbar site, and limbs, with less than 5% located in the head site. 4…”
Section: Letter To the Editormentioning
confidence: 99%
“…There is growing evidence indicating that the health consequences of pain are associated with the onset and progression of dementia (Whitlock et al 2017 ; Belin and Gatt 2006 ; Wang et al 2022 ; Wang and Liu 2021 ; Khalid et al 2022 , 2020 ; Innes and Sambamoorthi 2020 ; Whitlock et al 2017 Aug 1b ; Rouch et al 2022 ; Tzeng et al 2018 ; Cheng et al 2022 ; Kao et al 2021 ; Hurh et al 2022 ; Morton et al 2019 ; Hagen et al 2014 ; Islamoska et al 2020 ; George et al 2020 ; Lee et al 2019 ; Kostov et al 2019 ; Chen et al 2018 ; Huang et al 2015 ), which is a critical issue. Neurodegenerative diseases, such as Alzheimer’s disease and related dementias, are increasingly prevalent worldwide due to the rapid aging of the global population.…”
Section: Introductionmentioning
confidence: 99%
“…Although pain has been associated with worse cognition, [2][3][4][5][6][7] cognitive impairment, 7,8 and dementia, 2,5,9 some recent studies have not found a relationship between pain and cognitive decline 10 or dementia. 11 Such mixed findings may be due to varying definitions of pain, cognitive impairment, and dementia. Pain interference, defined as pain that limits a person's daily activities, may be a more important risk factor for cognitive impairment than pain severity.…”
Section: Introductionmentioning
confidence: 99%
“…Pain, which is common among older adults, may potentially be a modifiable risk factor for dementia. Although pain has been associated with worse cognition, 2–7 cognitive impairment, 7,8 and dementia, 2,5,9 some recent studies have not found a relationship between pain and cognitive decline 10 or dementia 11 . Such mixed findings may be due to varying definitions of pain, cognitive impairment, and dementia.…”
Section: Introductionmentioning
confidence: 99%